Endophytic Actinobacteria from Rhododendron spp. as an Antibacterial Agent - Risa Fitriandini; Sri Budiarti; Yulin Lestari (Biosaintifika: Journal of Biology & Biology Education)
Rhododendron has long been known to treat various diseases including diarrhea, but diversity and potency of its endophytic actinobacteria has not been studied. The objectives of this research were to explore the existence of endophytic actinobacteria from Rododendron spp. and assesed their antibacterial activity, as an effort to control the growth of bacterial pathogen resistant to some antibiotics. The endophytes were isolated from Rhododendron spp. using HV medium, and purified in ISP2 medium.  The antibacterial activity was assayed against Enteropathogenic Escerichia coli (EPEC) K1.1 resistant to ampicillin and Bacillus pumilus.  The Minimum Inhibitory Concentration (MIC) value, macroscopic and microscopic were examined. Twenty three of endophytic actinobacteria were successfully isolated from 7 Rhododendron species. Two of them, i.e.  RJkb1 and RJkb3 isolates, had high antibacterial activity, with 17.2 mm and 14.5 mm inhibition zone against EPEC K1-1, respectively; and 12.4 mm and 16.1 mm inhibition zone against B. pumilus, respectively.  The highest antibacterial activity for both RJkb1 and RJkb3 isolates was achieved at day 15, at 28 oC. At 250 µg/mL to 1750 µg/mL either RJkb1 or RJkb3 supernatant showed no activity against EPEC K1-1. The MIC value against B. pumilus was at 1250 µg/mL for both tested isolates. Under an electron microscope observation, cell morphology of the treated B. pumilus showed elongated cells and viewer in cell number, compared with the untreated one.  From this work, the existence of endophytic actinobacteria from Rhododendron spp. and their antibacterial activity contribute to the understanding of their diversity and potency as antibacterial agent.